2015
DOI: 10.1016/j.celrep.2015.08.060
|View full text |Cite
|
Sign up to set email alerts
|

Large Polyglutamine Repeats Cause Muscle Degeneration in SCA17 Mice

Abstract: SUMMARY In polyglutamine (polyQ) diseases, large polyQ repeats cause juvenile cases with different symptoms than adult-onset patients, who carry smaller expanded polyQ repeats. The mechanisms behind the differential pathology mediated by different polyQ repeat lengths remain unknown. By studying knock-in mouse models of spinal cerebellar ataxia-17 (SCA17), we found that a large polyQ (105 glutamines) in the TATA box-binding protein (TBP) preferentially causes muscle degeneration and reduces the expression of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
51
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 45 publications
3
51
0
Order By: Relevance
“…SMAD3 was essential for regulating muscle growth by interacting with other muscle specific regulatory factors (Liu et al 2001;Ge et al 2011;Sriram et al 2014). It was known that muscle development and growth could partly determine body weight in animals (Huang et al 2015). Thus, the current observations in this study together with previous studies raised the possibility that SMAD3 was a potential mediator of bovine body weight and phenotype.…”
Section: Discussionsupporting
confidence: 52%
“…SMAD3 was essential for regulating muscle growth by interacting with other muscle specific regulatory factors (Liu et al 2001;Ge et al 2011;Sriram et al 2014). It was known that muscle development and growth could partly determine body weight in animals (Huang et al 2015). Thus, the current observations in this study together with previous studies raised the possibility that SMAD3 was a potential mediator of bovine body weight and phenotype.…”
Section: Discussionsupporting
confidence: 52%
“…In 2011, a knock‐in mouse model of SCA17 was generated and expected to most closely recapitulate SCA17 genetically (Huang et al, ). This knock‐in SCA17 mouse model uses the Cre‐loxP technique, which allows for tissue‐ and time‐specific expression of mutant TBP (Yang et al, ; Huang et al, ). In the knock‐in mouse model, the mouse TBP exon 2 was replaced with human TBP exon 2 carrying 105 CAGs (Huang et al, ).…”
Section: Generation Of Sca17 Animal Modelsmentioning
confidence: 99%
“…In 2015, Huang et al reported the generation of germline TBP knock‐in mice by crossing the floxed TBP mice with transgenic mice expressing Cre under the control of the EIIa promoter, which drives the expression of Cre in early embryonic cells. Therefore, mutant TBP can be expressed ubiquitously at the endogenous level in the crossed mice (Huang et al, ). In this mouse model, the presence of mutant TBP reduced the level of wild‐type TBP in mouse brains, which was also reported previously in the transgenic mice, indicating that TBP is an important transcriptional regulator and that its protein level is tightly controlled in the body.…”
Section: Generation Of Sca17 Animal Modelsmentioning
confidence: 99%
See 2 more Smart Citations